2019
DOI: 10.1167/iovs.18-25837
|View full text |Cite
|
Sign up to set email alerts
|

Pulling and Tugging on the Retina: Mechanical Impact of Glaucoma Beyond the Optic Nerve Head

Abstract: Several retinal conditions have been recently revealed by optical coherence tomography (OCT) to occur more frequently in glaucoma than in healthy eyes: paravascular defects, peripapillary retinoschisis, and pseudo-cysts of the inner nuclear layer (INL). Here the clinical OCT findings described in these reports are reviewed and a framework that could explain why they are related and occur more frequently in glaucoma is proposed. Evidence suggests that these conditions all share in common a strong tendency to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 83 publications
(133 reference statements)
0
24
0
Order By: Relevance
“…For example, we previously proposed that ONH prelaminar schisis may include detachment of the blood vessels and aspects of their adventitia from the glio-fibrillar meniscus of Kuhnt, the ILM of Elschnig, and in some cases also from underlying prelaminar tissue as posterior deformation of the ONH progresses -because the blood vessels are tethered throughout the retina and might thus be limited in how far posteriorly they can be displaced as "cupping" progresses. 10 We surmised this initially from scrutiny of structural OCT scans. However, Figure 7 shows an OCTangiography scan from an eye with prominent signs of ONH prelaminar schisis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, we previously proposed that ONH prelaminar schisis may include detachment of the blood vessels and aspects of their adventitia from the glio-fibrillar meniscus of Kuhnt, the ILM of Elschnig, and in some cases also from underlying prelaminar tissue as posterior deformation of the ONH progresses -because the blood vessels are tethered throughout the retina and might thus be limited in how far posteriorly they can be displaced as "cupping" progresses. 10 We surmised this initially from scrutiny of structural OCT scans. However, Figure 7 shows an OCTangiography scan from an eye with prominent signs of ONH prelaminar schisis.…”
Section: Discussionmentioning
confidence: 99%
“…10 In that review article, we also reported several cases in which the ONH prelaminar tissue had exhibited OCT signs of "schisis" or splitting in association with variants of retinal anatomical disruption in glaucomatous eyes, such as peripapillary retinoschisis and paravascular defects. 10 While it will likely be informative to eventually determine whether there is an association between those (or other) retinal abnormalities and the ONH prelaminar schisis sign, it is more immediately important to determine if ONH prelaminar schisis occurs more frequently in glaucomatous eyes than in healthy eyes and whether its presence and/or apparent severity is associated with the degree of glaucomatous damage. Therefore, the purpose of this study was to compare the frequency of observing ONH prelaminar schisis by OCT in glaucoma and glaucoma suspect eyes versus healthy control eyes and to assess the association between ONH prelaminar schisis and other markers of glaucoma severity.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…25,[27][28][29] Optical coherence tomography shows that when adduction exceeds 26 degrees, 30 deformations of the ON head and Bruch's membrane greatly exceed those during extreme IOP elevation, 31 or deformations recently proposed as pathological to retina. 32 The human horizontal oculomotor range is ± 55 degrees, meaning that people can maximally abduct and adduct to that angle. 33,34 Although eye movements are usually smaller during sedentary activities or when the head is restrained in the laboratory or clinic, saccades and vestibular quick phases of 25 to 45 degrees are intrinsic to the large gaze shifts that are typical when the head and body are unrestrained.…”
mentioning
confidence: 99%